Identification of Agro-industrial project in the rural areas of Kano State of Nigeria - centre for agricultural development (Nig.) Ltd. (Ibadan centre for agricultural development (Nig.) Ltd., 1980)
This book examines the agro-allied industry in selected northern states of Nigeria. The reports highlights is divided into two parts. I. It described the inter alia and general operational systems for the agro-industries proposed; II contains an individual reports for Bauchi, Borno, Kaduna and Kano States, respectively
asm; 17/04/19
Loans
Keywords: Rural development; Nigeria